Lezioni di poesia - Stefania, Pavan (Biblioteca di Studi di Filologia Moderna, 2006)
This book focuses upon an aspect which has been little investigated to date in the poetics of Iosif Brodskij: the rich intertextual network that links his verses to classical literature. Brodskij's intertext never appears as imitation but rather as mimesis, like an inescapable mediation - at times concealed by the presence of cultures diachronically closer, the Russian in the first place - strongly impregnated with meaning and teaching: "(As for creation, the pen has created very little). / But how much light it casts in the night, / the ink, merging with the darkness!". This book proposes moments of reflection on the intense and nuanced relation that connects Brodskij's poetics with the poetics of Aristotle, and the subtle but equally strong links of Brodskij's idea of democracy with that of the organisation of government in Plato's Republic. Pursuing an historic approach, the book delineates the characteristics of Brodskij as a reader of the classics and, at the same time, as a person intimately involved, at an individual and collective level, in the events of Russian culture. In Brodskij's dialogical approach, in particular in relation to ancient classical culture, the lineaments of the poet emerge clearly. Considered in their globality, these reveal inspiration, thought (profound, and strongly impregnated with philosophy), moral rigour (ironic and self-ironising), the renunciation of the display of feelings, and the tension towards an autobiographical writing that is universalised and externalised, a strong and constant link with the narration of myths and, in a manner that is increasingly marked over the time of his life and work, a progressive prevalence of the signs of the classical authors.